THE CHEMICAL ANALYSIS OF GALL STONES IN THE SOUTHEAST TURKEY - Halil DEĞERTEKİN and Özden UZUNALİMOĞLU and Bülent ALIÇ and Samet AKBABA and Vedat GÖRAL and Güler GÖYMEN and Meral HOŞCAN (Turkish Journal of Gastroenterology, 2020)
-